Involuntary mental health treatment in the era of the United Nations Convention on the Rights of Persons with Disabilities - Mahomed, Faraaz; Stein, Michael Ashley; Patel, Vikram (PLOS Medicine, 2018)
Based on interviews with a variety of participants, Vikram Patel and colleagues advocate for philosophical and practical progress toward recognizing decision-making capacity in people with psychosocial disabilities.